2011
DOI: 10.1186/1746-1596-6-s1-s13
|View full text |Cite
|
Sign up to set email alerts
|

Five years of experience teaching pathology to dental students using the WebMicroscope

Abstract: BackgroundWe describe development and evaluation of the user-friendly web based virtual microscopy - WebMicroscope for teaching and learning dental students basic and oral pathology. Traditional students microscopes were replaced by computer workstations.MethodsThe transition of the basic and oral pathology courses from light to virtual microscopy has been completed gradually over a five-year period. A pilot study was conducted in academic year 2005/2006 to estimate the feasibility of integrating virtual micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 14 publications
4
55
0
2
Order By: Relevance
“…Instructors appreciate the ability to point out and compare features on the virtual microscope to multiple students at the same time, increasing collaboration among faculty and students (Braun and Kearns, 2008;Husmann et al, 2009;Triola and Holloway, 2011). Access to the virtual microscope outside of scheduled class time has also been cited as an advantage of the virtual microscope (Blake et al, 2003;Bloodgood and Ogilvie, 2006;Kumar et al, 2006;Husmann et al, 2009;Merk et al, 2010;Szymas and Lundin, 2011). A web-based virtual microscope also opens up the opportunity to teach histology across several campuses, locations, or even countries while using the same teaching material, creating a more equal learning experience for the students and minimizing the cost of maintaining the virtual microscopy program (Lundin et al, 2008;Pinder et al, 2008) Although the majority of studies have focused on the implementation of the virtual microscope into the medical school curriculum (Harris et al, 2001;Blake et al, 2003;Krippendorf and Lough, 2005;Bloodgood and Ogilvie, 2006;Merk et al, 2010;Paulsen et al, 2010;Triola and Holloway, 2011), recent studies are emerging that assess the utility of integrating virtual histology into the undergraduate curriculum as well (Husmann et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Instructors appreciate the ability to point out and compare features on the virtual microscope to multiple students at the same time, increasing collaboration among faculty and students (Braun and Kearns, 2008;Husmann et al, 2009;Triola and Holloway, 2011). Access to the virtual microscope outside of scheduled class time has also been cited as an advantage of the virtual microscope (Blake et al, 2003;Bloodgood and Ogilvie, 2006;Kumar et al, 2006;Husmann et al, 2009;Merk et al, 2010;Szymas and Lundin, 2011). A web-based virtual microscope also opens up the opportunity to teach histology across several campuses, locations, or even countries while using the same teaching material, creating a more equal learning experience for the students and minimizing the cost of maintaining the virtual microscopy program (Lundin et al, 2008;Pinder et al, 2008) Although the majority of studies have focused on the implementation of the virtual microscope into the medical school curriculum (Harris et al, 2001;Blake et al, 2003;Krippendorf and Lough, 2005;Bloodgood and Ogilvie, 2006;Merk et al, 2010;Paulsen et al, 2010;Triola and Holloway, 2011), recent studies are emerging that assess the utility of integrating virtual histology into the undergraduate curriculum as well (Husmann et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Web-based virtual microscopy provides a platform similar to the optical microscope to study tissues, allowing movement of the ''slide'' in order to examine multiple sections of the tissue and allows for changes in magnification. Virtual microscopy has been adapted to several higher-level professional programs, such as medical (Blake et al, 2003;Krippendorf and Lough, 2005;Helle et al, 2011), dental (Szymas and Lundin, 2011), graduate residency programs (Bruch et al, 2009;Koch et al, 2009) and veterinary schools (Mills et al, 2007), and specifically to courses like medical histology (Scoville and Buskirk, 2007;Schmidt et al, 2011), pathology (Dee and Meyerholz, 2007;Braun and Kearns, 2008;Cunningham et al, 2008;Kim et al, 2008), dental histology (Weaker and Herbert, 2009), and veterinary cytopathology (Neel et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…All studies agree that WSI improves collaboration between students and self-learning [6,9,16,24,33,34]. Teachers also positively evaluate WSI because, although there is initially a significant increase in the time related to the preparation of the material, in the end it results in a significant reduction in the time spent in the preparation of the lessons [19,35]. WSI provides a more complete approach to the cases by adding clinical information, radiological imaging, macroscopic images, immunohistochemical stains and molecular data to the virtual histological images [33,36].…”
Section: Wsi In Undergraduate Teachingmentioning
confidence: 99%
“…Many of these centers have evaluated the opinion of students after the introduction of WSI, and all have reported very positive feedback [9,26,30,31]. One of the most valued advantages is the improved accessibility to the slides with WSI, allowing the student to access the slides at any time and from any place [10,14,19]. Several studies have shown that this is one of the most appreciated features of WSI, and this was the most prized feature in a study conducted at our institution [10].…”
Section: Wsi In Undergraduate Teachingmentioning
confidence: 99%
See 1 more Smart Citation